Structural characterization of the heme-based oxygen sensor, AfGcHK, its interactions with the cognate response regulator, and their combined mechanism of action in a bacterial two-component signaling system - Stranava, Martin; Martínek, Václav; Man, Petr; Fojtikova, Veronika; Kavan, Daniel; Vaněk, Ondřej; Shimizu, Toru; Martinkova, Marketa (Proteins, 2016)
The oxygen sensor histidine kinase AfGcHK from the bacterium Anaeromyxobacter sp. Fw 109-5 forms a two-component signal transduction system together with its cognate response regulator (RR). The binding of oxygen to the heme iron of its N-terminal sensor domain causes the C-terminal kinase domain of AfGcHK to autophosphorylate at His183 and then transfer this phosphate to Asp52 or Asp169 of the RR protein. Analytical ultracentrifugation revealed that AfGcHK and the RR protein form a complex with 2:1 stoichiometry. Hydrogen-deuterium exchange coupled to mass spectrometry (HDX-MS) suggested that the most flexible part of the whole AfGcHK protein is a loop that connects the two domains and that the heme distal side of AfGcHK, which is responsible for oxygen binding, is the only flexible part of the sensor domain. HDX-MS studies on the AfGcHK:RR complex also showed that the N-side of the H9 helix in the dimerization domain of the AfGcHK kinase domain interacts with the helix H1 and the β-strand B2 area of the RR protein's Rec1 domain, and that the C-side of the H8 helix region in the dimerization domain of the AfGcHK protein interacts mostly with the helix H5 and β-strand B6 area of the Rec1 domain. The Rec1 domain containing the phosphorylable Asp52 of the RR protein probably has a significantly higher affinity for AfGcHK than the Rec2 domain. We speculate that phosphorylation at Asp52 changes the overall structure of RR such that the Rec2 area containing the second phosphorylation site (Asp169) can also interact with AfGcHK. Proteins 2016; 84:1375-1389. © 2016 Wiley Periodicals, Inc.
Keywords: sekundární struktura proteinů; hydrogen-deuterium exchange; histidine kinase; signální transdukce; vodík-deuteriová výměna; Phosphorylation; rekombinantní proteiny; two-component signal transduction system; homology modeling; Signal Transduction; Deuterium Exchange Measurement; protein-protein docking; železo; strukturní homologie proteinů; heme-based oxygen sensor; Aspartic Acid; Cloning, Molecular; analytical ultracentrifugation; Aeromonas salmonicida; Protein Domains; hem; Bacterial Proteins; Heme; Iron; kyslík; protein-protein interaction; Escherichia coli; Protein Structure, Secondary; kyselina asparagová; Histidine Kinase; histidin; Structural Homology, Protein; klonování DNA; fosforylace; histidinkinasa; Oxygen; Histidine; bakteriální proteiny; Myxococcales; proteinové domény; Recombinant Proteins